2009
DOI: 10.1002/ar.20960
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Development and Skeletogenesis of the Pharyngeal Jaw Apparatus in the Cichlid Nile Tilapia (Oreochromis niloticus)

Abstract: The evolution of a specialized pharyngeal jaw apparatus (PJA) has been argued to be the key evolutionary innovation that allowed the explosive adaptive radiation of cichlid fishes in East African lakes. Subsequent studies together with recent molecular phylogenies have shown that similar innovations evolved independently several times within the teleosts, which poses the questions: (1) how similar are the developmental mechanisms responsible for these changes in divergent taxa and (2) how did such complex feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…These include 40 S and 60 S ribosomal proteins (duplicated in R. “chilingali” and M. estherae ), claudin 29a ( M. estherae ), GTPase IMAP family member 7 ( P. similis ), C–type lectin domain family 4 ( M. estherae ), high-mobility group 20B (HMG20B) from HMG-box superfamily ( A. tweddlei ), and hox gene cluster genes (all species). Hox genes are important in the regulation of development, and have been found to be associated with differential jaw development in cichlid fishes [49,50]. An immunoglobulin light chain gene belonging to the largest gene family represented in this study was found duplicated in P. similis .…”
Section: Discussionmentioning
confidence: 74%
“…These include 40 S and 60 S ribosomal proteins (duplicated in R. “chilingali” and M. estherae ), claudin 29a ( M. estherae ), GTPase IMAP family member 7 ( P. similis ), C–type lectin domain family 4 ( M. estherae ), high-mobility group 20B (HMG20B) from HMG-box superfamily ( A. tweddlei ), and hox gene cluster genes (all species). Hox genes are important in the regulation of development, and have been found to be associated with differential jaw development in cichlid fishes [49,50]. An immunoglobulin light chain gene belonging to the largest gene family represented in this study was found duplicated in P. similis .…”
Section: Discussionmentioning
confidence: 74%
“…(a) Puntius semifasciolatus stages 1-6 are notochord length (L N ) and stages 7-18 are standard length (L S ); stages 12 and 13 are both 6·03 mm, but are different ages (Appendix); never ossifies: ebc5, hbc4, pbc4, pc. (b) Barbus barbus; *, unclear from Vandewalle et al (1992) in which specific epibranchials are ossifying; **, these are ossified elements that were not discussed by Vandewalle et al (1992) but ones that were observed in this study in an adult specimen (USNM 204120, 83.5 mm); the development of the fifth ceratobranchial bone in larval fishes (Gonzalez et al, 1996;Le Pabic et al, 2009). The 18 marker elements, representing the 18 stages of ossification observed in P. semifasciolatus, were the fifth ceratobranchial bone, premaxilla, anterior ceratohyal, urohyal, dorsal hypohyal bone, symplectic, interhyal bone, metapterygoid, subopercle, autopalatine, coronomeckelian, first basibranchial bone, first epibranchial bone, third basibranchial bone, third hypobranchial bone, first hypobranchial bone, third pharyngobranchial bone and second pharyngobranchial bone [ Fig.…”
Section: Resultsmentioning
confidence: 79%
“…These studies have uncovered differences in the location of tooth fields, the arrangement and number of teeth in tooth families, and the positioning and modes of tooth replacement. The spatiotemporal pattern of early tooth positioning within developing tooth fields has also been studied in many of these models (Huysseune et al, 1998;Van der heyden and Huysseune, 2000;Debiais-Thibaud et al, 2007;Stock, 2007;Le Pabic et al, 2009;Atukorala and Franz-Odendaal, 2014) with major differences found in the sequence and pattern of early tooth formation. Collectively, these studies highlight the diversity of tooth patterning and replacement mechanisms among teleosts.…”
Section: Introductionmentioning
confidence: 99%